26.2k views
0 votes
Solve the equation below for x.
| 2(x+5)= 3(x-4)​

User SIGSTP
by
6.2k points

2 Answers

3 votes

Answer:

x=22

Explanation:

2(x+5)=3(x-4)

2x+10=3x-12

-x=-22

x=22

User Artur Smirnov
by
6.3k points
2 votes

Step 1: Distribute the numbers outside the parentheses to each number inside the parentheses

(2 * x) + (2 * 5) = (3 * x) + (-4 * 3)

2x + 10 = 3x - 12

Step 2: Combine like terms

2x goes with 3x. To do this subtract 2x to both sides (subtraction is the opposite of addition)

(2x - 2x) + 10 = (3x - 2x) - 12

0 + 10 = x - 12

10 = x - 12

10 goes with -12. To do this add 12 to both sides (addition is the opposite of subtraction)

10 + 12 = x + (-12 + 12)

22 = x + 0

22 = x

Check:

2(22 + 5) = 3(22 - 4)

2(27) = 3(18)

54 = 54

Hope this helped!

~Just a girl in love with Shawn Mendes

User Hyamanieu
by
6.0k points